ENVIRONMENTAL EFFECTS ON GROWTH TRAITS OF TEDDY GOATS - Z. H. Kuthu; K. Javed . M. E. Babar; Abdul Sattar; M. Abdullah (Journal of Animal and Plant Sciences, 2013)
Data on 18702 kidding, performance and pedigree records of 5150 Teddy goats and progeny of 382 sires maintained as separate flocks at Livestock Experiment Stations: Rakh Ghulaman, District Bakkhar, Rakh Khariewala, District Layyahand and Chak Katora, District Bahawalpur, Punjab, Pakistan during the period 1972-2008 were utilized to study the phenotypic performance and environmental sources of variation on different growth traits. Statistical analyses were carried out by using mixed model procedure of the SAS statistical package program. The least squares means for birth weight (BWT), weaning weight (WWT), six month weight (6WT), nine month weight (9WT) and yearling weight (YWT) were 1.66±0.003, 9.59±0.01, 11.70±0.02, 16.69±0.02 and 21.03±0.03 kg, respectively. Least squares analysis revealed a significant (P<0.01) effect of year and season of birth, sex, flock and type of birth on BWT and WWT. The effect of flock, year and type of birth was significant (P<0.01) on 6WT, 9WT and YWT. Season of birth had a significant effect on YWT; however its effect on 6WT and 9WT was non-significant. The effect of BWT and WWT was significant (P<0.01) on 6WT and 9WT and YWT. A significant interaction (P<0.01) was noticed between sex and type of birth for birth weight and weaning weight, while the interaction was non-significant between season of birth and sex. The findings of this study revealed that improvement in growth traits is possible by minimizing the effect of environmental sources.
Keywords: Teddy goats; growth traits; environmental effects